Agregacja budżetów centrów zysku wspomagana Ms Excel - Kujawski, Jarosław (MS Excel-aided aggregation of profit centres budgets, 2008)
The paper presents a concept of MS Excel-aided system of aggregation of budgets for profit cen très. The core assumptions of the concept are: an identical layout of all budgets, blocking thé budg positions that are not available to be budgeted and the application of special global sum function buili in the spreadsheet Automated summing of budgets is not obstructed by adding newly-created cutting unnecessary budgets thanks to the dedicated mechanism of sheets and file management. The presented IT tool has been tailor-made to the medium-sized enterprise operating in the elec tro-mechanics sector. It makes possible for 10 responsible persons to manage several budgets o 5 MB disk memory.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 239-248